Method and software for photon dose calculation in phantoms of human body - V. Yu. Golikov (Радиационная гигиена)
The current study is focused on the development of the method of the calculation of the dose quantities required for the assessment or limitation of the ionizing exposure (mean organ doses, effective dose, distribution of the absorbed dose in the critical organ) based on the measured characteristics of the fields of the photon computational (kerma free-in-air, readings of the individual dosimeters) with the energy of 0,02-10 mEv. The dedicated software was developed based on the results of the study, allowing estimating the values of more than 20 mean organ doses, effective dose and the distribution of the absorbed dose in the red bone marrow in 8 computational children and adult models. Additionally, it is possible to calculate the ratios of the effective dose to the readings of the “individual dosimeters”, placed in 48fixed points on the phantom surface. The developed method and software can be used for: (1) calculation of the doses from external exposure and estimation of the level of the radiation injuries in case of the acute radiation exposure of the staff and public; (2) development of the models of the exposure of the staff working in the radiation fields with non-uniform distribution of their characteristics; (3)planning of the countermeasures for the remediation of the consequences of the radioactive contamination (calculation of the routes and working time in contaminated zones); (4) education and training of the staff participating in the investigation and remediation of the consequences of the radioactive contamination.